A MODEL OF INNOVATIVE CAPABILITY IMPROVEMENT THROUgH AFFECTIVE COMMITMENT, KNOWLEDgE SHARINg AND ISLAMIC LEADERSHIP IN CIVIL SERVANT STAFF (PNS) OF SEMARANg REgENCY - Devi Agustini; Heru Sulistyo (IJIBE (International Journal of Islamic Business Ethics), 2017)
The primary purpose of this study was to test a model in which knowledge sharing, Islamic leadership, and meaning in life predict affective commitment and innovative capability. A total of 119 respondents completed questionnaires on knowledge sharing, Islamic leadership, meaning in life, affective commitment, and innovative capability. Results from structural equation modeling based smartPLS 3.0 confirmed that 1) knowledge sharing and Islamic leadershipwere were positively related to affective commitment and innovation capability; 2) affective commitment was positively related to innovation capability; and 3) meaning in life moderated the relationships between Islamic leadership and affective commitment.Keywords: Knowledge sharing, Islamic leadership, Meaning in life, Affective commitment, Innovative capability.